Aggregation and conformational changes of silver carp myosin as affected by the ultrasound–calcium combination system. (13th July 2018) - An, Yueqi; Liu, Qing; Xie, Yaru; Xiong, Shanbai; Yin, Tao; Liu, Ru
Abstract: BACKGROUND: Ultrasound and Ca 2+ have been used separately to increase myosin properties in fish processing. However, little is know about how myosin changes are affected by Ca 2+ and ultrasound in combination. The present study aimed to investigate the effects of the ultrasound–calcium combination system on aggregation and conformational changes of silver carp myosin. RESULTS: Ultrasound facilitated a Ca 2+ ‐induced increase in turbidity. As the Ca 2+ concentration increased from 0 to 100 mmol L −1, there was an obvious increase in the turbidity, solubility and mean hydrated particle size of myosin after ultrasound treatment compared to without treatment. Moreover, changes of total and reactive SH contents depended on the ultrasound–calcium combination conditions. Under this combination system, myosin surface hydrophobicity significantly increased for the synergistic effect of ultrasound and Ca 2+ . Furthermore, the ultrasound–calcium combination conditions could affect myosin gelation, with better gelation properties being observed for myosin treated with a combination of 60 mmol L −1 Ca 2+ and 9 min of ultrasound. CONCLUSION: The combination system reported in the present study was beneficial for myosin unfolding, facilitating intermolecular interactions between Ca 2+ and myosin. Ultrasound treatment promoted myosin aggregation via the induction of Ca 2+ and reduced the critical concentration of Ca 2+ required to aggregate myosin. In the fish processing industry, this combination system can enhance the gelation properties of surimi‐based products. © 2018 Society of Chemical Industry